P5 A Cut Throat approach to post thyroidectomy care. (8th April 2021) - McGovern, J; Kurup, V J; Bhaskar, P; Slinger, C A; McGovern, Julia
Abstract: Introduction: Across the UK, approximately 10, 000 elective neck dissection surgeries (thyroidectomy/parathyroidectomy) are performed each year. The recognised post-operative complications of such surgeries range from mild post-operative hypocalcaemia to life threatening wound haematoma . Aim: This project aimed to establish the awareness of the British Association of Endocrine and Thyroid Surgeons (BAETS) post thyroidectomy guidelines and provide targeted education in order to improve any identified failings in the management of this patient group. Methods: A nine point questionnaire was generated based on the guidelines published by BAETS. This questionnaire was disseminated to the junior doctors and nurse practitioners based on the surgical unit of North Tees General Hospital. Results: Results were analysed from twenty respondents. 92% opted to call a registrar or consultant during a critical airway emergency secondary to wound haematoma rather than attempt to open the wound on the ward. Respondents displayed poor understanding of the risks of thyroid surgery (55%) and struggled to identify symptoms of hypocalcaemia (25%). Participants showed good understanding of the need for post-operative thyroxine (100%), the correct dose of calcium gluconate required for treatment of hypocalcaemia (90%) and normal calcium levels (85%). A video was created and distributed which highlighted front of neck anatomy and steps involved in releasing a wound haematoma. This included the 'SCOOP' video created by Endocrine Surgery Oxford. Data collected following the session found 93% of respondents would be more confident to intervene in future. Conclusion: It is vital that junior doctors are well educated and equipped to deal with post-operative patients, especially those who may develop imminent airway obstruction. Our "cut throat" approach aims to ensure our first responders are decisive and effective in carrying out life saving interventions.